Situation of Sectors Financed by Participation Banks: 2015-2019 Period Analysis - Alp Aytaç; Ümit Gücenme Gençoğlu; Süleyman Hakkı Ayhan (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Participation Banks refers to the organizations that operate with the principle of collecting funds and extending loans through special current and participation accounts and the branches in Turkey of such organizations established abroad. The main aim of this research is to shed light on which sectors are financed by participation banks. To accomplish this aim, data covering the 2015-2019 period is used in this research. State-funded participation banks such as Vakıf and Ziraat established in 2015 is the reason why authors examined the 2015-2019 period. Data was downloaded from the Participation Banks Association of Turkey website, and it is prepared at the end of 2019. In this study, situation analysis is used to show the development of participation banks and the sectors they finance. In this context, the growth in terms of the number of branches and personnel, the change in basic indicators, and the financed sectors' situation were determined in the examined period. Results show that participation banks have increased their role in the banking system. In addition, there is a relation between their growth and funding and fundraising levels. It is found that participation banks mainly finance construction sector which have an essential effect on the macroeconomic growth of the Turkish economy.